Successful Primary Percutaneous Coronary Intervention without Stenting: Insight from Optimal Coherence Tomography - Roh, Ji Woong; Kim, Yongcheol; Lee, Oh-Hyun; Im, Eui; Cho, Deok-Kyu; Choi, Donghoon (Yonsei medical journal, 2022)
For patients with acute myocardial infarction, current management guidelines recommend implantation of a drug-eluting stent, dual antiplatelet therapy (including potent P2Y12 inhibitors) for at least 1 year, and maintenance of life-long antiplatelet therapy. However, a pilot study showed favorable results with antithrombotic therapy without stent implantation when plaque erosion, not definite plaque rupture, was confirmed using optical coherence tomography (OCT), despite the patients having acute myocardial infarction. Here, we present a case where successful primary percutaneous coronary intervention was performed without stenting with the aid of OCT in a patient with ST-elevation myocardial infarction who developed thrombotic total occlusion of the right coronary artery.